Transformative pathways to sustainability Learning across disciplines, cultures and context - Ely, Adrian (Pathways to Sustainability, 2022)
Transformations to sustainability are increasingly the focus of research and policy discussions around the Sustainable Development Goals. However, the different roles played by transdisciplinary research in contributing to social transformations across diverse settings have been neglected in the literature. Transformative Pathways to Sustainability responds to this gap by presenting a set of coherent, theoretically informed and methodologically innovative experiments from around the world that offer important insights for this growing field. The book draws on content and cases from across the 'Pathways' Transformative Knowledge Network, an international group of six regional hubs working on sustainability challenges in their own local or national contexts. Each of these hubs reports on their experiences of 'transformation laboratory' processes in the following areas: sustainable agricultural and food systems for healthy livelihoods, with a focus on sustainable agri-food systems in the UK and open-source seeds in Argentina; low carbon energy and industrial transformations, focussing on mobile-enabled solar home systems in Kenya and social aspects of the green transformation in China; and water and waste for sustainable cities, looking at Xochimilco wetland in Mexico and Gurgaon in India. The book combines new empirical data from these processes with a novel analysis that represents both theoretical and methodological contributions. It is especially international in its scope, drawing inputs from North and South, mirroring the universality of the Sustainable Development Goals. The book is of vital interest to academics, action researchers and funders, policy makers and civil-society organisations working on transformations to sustainability.